Assessing species at risk legislation across Canadian provinces and territories - Susan C.C. Gordon; Adam G. Duchesne; Michael R. Dusevic; Carmen Galán-Acedo; Lucas Haddaway; Sarah Meister; Andrea Olive; Marlena Warren; Jaimie G. Vincent; Steven J. Cooke; Joseph R. Bennett (Canadian Science Publishing, 2024)
Canada's provinces and territories govern species at risk across most of Canada, with the federal Species at Risk Act generally covering only aquatic species, migratory birds, and species living on federal land. More than a decade after a 2012 report by the environmental law charity Ecojustice on species at risk protection in Canada, we use the same criteria to evaluate the current state of provincial and territorial species at risk legislation, and we provide updates on changes in each jurisdiction since 2012. These criteria are as follows: whether at-risk species are being identified, whether these species are being protected, whether their habitat is being protected, and whether species recovery plans are being created and implemented. We find that there is considerable variation across jurisdictions, with shortcomings that result in inadequate protections for at-risk species, as well as strong components that should be adopted by all jurisdictions. We recommend seven key areas for improvement: dedicated and harmonized legislation, limited discretionary power, increased embrace of scientific and Indigenous knowledge, appropriate timelines for actions, reasonable exemptions to protections, habitat protection across land ownership types, and transparency throughout the process. We urge policymakers to address current shortcomings as they work toward meeting Canada's biodiversity conservation commitments.